Women’s Language Used by Female Characters in the Movie How To Be Single - Putri Nila Sudewi, Ni Ketut (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p17, 2018)
This undergraduate thesis entitled Women’s Language Used by Female Characters in The Movie How To Be Single. It is aimed at identifying the language features applied by female characters and finding out the functions of each type of women’s linguistic features. This paper used the theory of women’s linguistic features proposed by Robin Lakoff (1975). The data source in this study is the movie How To Be Single.  The collected data were identified and selected, then the features of women’s language used by the female characters in the movie How To Be Single were analyzed  based on Lakoff (1975). The method applied in collecting data was the documentation method. Afterwards, the method of analyzing data in this study was the descriptive qualitative method. This study applied informal method in presenting the data analysis. The findings of the analysis showed that there were nine kinds of women’s linguistic features found in the movie How To Be Single. There were also some functions of women’s linguistic features found in the data. The functions of each type of the features are closely related to the context in which it is used. Each type of women’s linguistic features found in the movie displays has different functions and reasons.